Performance Increase of the Digital Fourier Filter in Measuring Bodies of Microprocessor Protections - V. Yu. Rumiantsev; Yu. V. Rumiantsev; F. A. Romaniuk; A. A. Dziaruhina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A technique for constructing a digital filter based on the discrete Fourier transform as part of microprocessor protections for electrical installations which is characterized by increased performance in the transient mode of setting its output signal is considered. To implement the filter, it is proposed to use the so-called equivalent orthogonal components of the input current or voltage signal which are a function of the current value of the nonlinear correction factor and the orthogonal components of the fundamental frequency signal isolated using a digital Fourier filter. The rate of change of equivalent orthogonal components in transient modes is determined by the nature of the change in the nonlinear correction factor. To form the latter, it is necessary to have two independent transition characteristics of the input signal. Previously, it was proposed to generate these characteristics using two digital filters, viz. the actual Fourier filter which extracts the actual value of the fundamental harmonic from the input signal and the additional filter which determines the actual value of the entire input signal. In this article, it is proposed to abandon the additional digital filter and determine the nonlinear correction factor, as well as the orthogonal components of the equivalent signal using a direct digital Fourier filter. A mathematical model of the developed filter and element models for reproducing test influences are implemented in the MATLAB-Simulink dynamic simulation environment. The operation of the digital Fourier filter model with accelerated operation in transient mode was tested using several types of test influences, viz. a sinusoidal signal with a frequency of 50 Hz, a signal with an aperiodic component, an influence with higher harmonics, as well as a signal close to the real secondary current of a short circuit current transformer. The computational experiments that had been conducted revealed a significant (up to 1.5–1.7 times) increase in the speed in the transient mode of the proposed digital filter compared to the standard Fourier filter.